1994
DOI: 10.1007/bf02168080
|View full text |Cite
|
Sign up to set email alerts
|

Child dissociation and the family context

Abstract: Forty boys and their parents completed measures of dissociation, state anxiety, and perceptions of parental behaviors. Mothers completed a behavior problems checklist about their sons. The results indicated a correspondence between fathers' and sons' dissociation scores. In addition, links were found between parental dissociation, parental inconsistency and rejection, and child dissociation. The findings are discussed in the context of several recently proposed models of the etiology of child dissociative diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…It has been used to examine parent involvement and strictness in relation to weight loss[48] and dietary behavior,[27, 28] and in children as young as 8 years old. [49] The 30-item version[50] was completed by the child and assesses three dimensions of parenting: Acceptance vs. rejection, Psychological control vs. autonomy, and Firm vs. lax control. Acceptance vs. rejection assesses the emotional aspects of parenting, i.e., displays of warmth and support.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used to examine parent involvement and strictness in relation to weight loss[48] and dietary behavior,[27, 28] and in children as young as 8 years old. [49] The 30-item version[50] was completed by the child and assesses three dimensions of parenting: Acceptance vs. rejection, Psychological control vs. autonomy, and Firm vs. lax control. Acceptance vs. rejection assesses the emotional aspects of parenting, i.e., displays of warmth and support.…”
Section: Methodsmentioning
confidence: 99%
“…Some research finds that parents who suffer from mental health problems are likely to be neglectful, abusive, and/or inconsistent in their parenting (Kluft, 1987). Inconsistent parenting can cause the child to be stressed and confused, which may lead to dissociative tendencies (Mann & Sanders, 1994). According to Kisiel and Lyons, "A natural, protective response to overwhelming traumatic experiences, dissociation can become an automatic response to stress" (2001, p. 1034).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Putnam (1997) analyzed the potential moderating roles of age, gender, culture, genetic factors, and education/intelligence and although moderating trends were found for some of these variables, existing research has not convincingly demonstrated that any of these variables significantly influence dissociation. In contrast, research has revealed a number of family environmental factors significantly associated with dissociation, including level of family risk (Malinosky-Rummel & Hoier, 1991), lack of parental care and warmth (Mann & Sanders, 1994; Modestin et al, 2002). inconsistent discipline (Braun & Sachs, 1985; Mann & Sanders, 1994), parental control (Modestin et al, 2002), and poor relationship between parents (Maaranen et al, 2004).…”
mentioning
confidence: 99%
“…In contrast, research has revealed a number of family environmental factors significantly associated with dissociation, including level of family risk (Malinosky-Rummel & Hoier, 1991), lack of parental care and warmth (Mann & Sanders, 1994; Modestin et al, 2002). inconsistent discipline (Braun & Sachs, 1985; Mann & Sanders, 1994), parental control (Modestin et al, 2002), and poor relationship between parents (Maaranen et al, 2004). All of these family factors are also associated with abusive environments (Wolfe, 1985).…”
mentioning
confidence: 99%